EXPLORING EXTENSIVE READING COMPREHENSION CLASS THROUGH PROJECT BASED-LEARNING - Anita Dwi Hapsari; Irmayani Irmayani (Edulitics (Education, Literature, and Linguistics) Journal, 2016)
Abstract: The development of information in digital era has shifted thestudents’ attitude and interest in reading novel. There are some courses thatdemand the skill of extensively reading particularly in English LanguageTeaching Department. In this paper, the writers highlight an alternativeapproach which can be done by the teacher to stimulate and enhance students’understanding about novel through a project-based learning. The literaryreview used in this paper are focusing the intrinsic elements of a novel which iswell-known as a part of literary work especially in prose that is character, plot,setting and conflict. The first step that must be taken is choosing the novel toread as a basic of project-based learning. Then the writers focus on intrinsicelements within. The writers simply discuss about four intrinsic elements of thestory. They are character, setting, plot and conflict. After the writers havediscussed one by one of intrinsic elements theory of the novel, the writers put inthe result of the study which is hoped suitable with the level or academiccompetence. So it seems like reading a novel with various language practices.The result of this idea, although there is no survey yet to measure how effectivethis product is, that this learning approach need to be applicated to enhance thestudents’ understand about literary. Practically, language competence can beexplored by the writer to be more creative in making useful learning productwhich can be used for learning English when the writer is graduated fromEnglish Department. Keywords: reading, novel, project-based learning